Pembelajaran Berbasis Heutagogi Di Pendidikan Tinggi Digital: Tinjauan Teoretis, Sintesis Literatur, Dan Implikasi Masa Depan - Ishaq, Ishaq (Jurnal Riset Evaluasi Pendidikan, 2024)
The rapid development of digital technology in higher education has driven the need for a new learning paradigm that is more student-centered and able to equip them with lifelong independent learning skills. Heutagogy or self-determined learning emerged as a continuation of andragogy in an effort to face these challenges. This review article discusses the theoretical basis of heutagogy along with related concepts such as andragogy, cybergogy, peeragogy, and synthesizes the latest research findings on the application of heutagogy-based learning in digital higher education environments. The literature review shows that the heutagogy approach with its characteristics of independent learning, deep reflection, non-linear learning, and capability development is increasingly relevant in the era of Education 4.0. Recent studies report the implementation of heutagogy principles in curriculum design, technology utilization (e.g. mobile learning, AR/VR, and artificial intelligence such as ChatGPT), and teacher training programs that generally have a positive impact on student engagement, self-regulation skills, and readiness for lifelong learning. The critical discussion in this article highlights gaps and challenges including educator readiness, curriculum adaptation needs, and infrastructure in identifying opportunities for broader implementation of heutagogy. The article concludes with practical implications and strategic recommendations for educators and policymakers to adopt heutagogy principles in creating an innovative, inclusive, and sustainable digital higher learning ecosystem in the future.